Impact of PPARA, PPARD and PPARG genetic variants on elite athletic performance: a systematic literature review - Bortkevic, A.; Gineviciene, V.; Utkus, A. (Sporto Mokslas-Sport Science, 2021)
Sports performance is an enormously complex multifactorial phenomenon, and is determined by numerous intrinsic and extrinsic factors as well as by the interaction between them. Genetic factors account for 44-68% of the variability of physical performance phenotypes, making an understanding of the genomic characteristics of elite athletes particularly important in sports theory, practice, and medicine. The coordinated changes in gene expression of response to training are regulated by transcriptional factors, such as PPARs gene family and their coactivators. Due to the importance of PPARs gene family for athlete`s adaptation, metabolism and energy homeostasis, and the lack of research that could summarize the latest available studies, the aim of this systematic review was to review the literature and determine which PPARs gene family polymorphisms PPARA rs4253778, PPARD rs2016520, PPARG rs1801282 are associated with elite sports performance.The systematic review was performed according to the PRISMA guidelines. The systematic computerized literature search was conducted in PubMed and the Web of Science databases, using a combination of the following search terms: PPAR, peroxisome proliferator activated receptor, sport, athlete, endurance, sprint, power, sport genomic, polymorphism. The study included 10 electronically published articles in English, selected according to the listed inclusion and exclusion criteria.In scientific publications, the authors analyzed PPARA rs4253778, PPARD rs2016520, PPARG r s1801282 polymorphisms in the main groups of athletes: (1) aerobic endurance sports, (2) sprint-power and (3) mixed (aerobic-anaerobic capacity) sports groups. In several articles, the authors analyzed the frequency distribution of genotypes and alleles among groups of elite, sub-elite, and non-elite athletes. Most of the research was conducted by scientists from Russia, Poland, Israel and Lithuania. The PPARA gene is one of the first identified gene candidates associated with physical ability and elite athlete status. A systematic review of the literature has shown that PPARA (rs4253778) C allele and G allele, and PPARG (rs1801282) Ala allele are associated with elite athlete status. The PPARA (rs4253778) C allele and PPARG (rs1801282) Ala allele are associated with sprint and power or mixed sports groups, and PPARA (rs4253778) G allele and PPARD (rs2016520) C allele are associated with endurance sports groups, while PPARD T allele is associated with mixed sports groups. But the significance of PPARD polymorphism for the physical performance of elite athletes is questionable, due to the small number of publications, and therefore additional studies with a larger cohort of subjects are needed.A systematic review of the literature showed that PPARs polymorphisms have an impact on the physical performance of elite athletes. PPARA (rs4253778) and PPARG (rs1801282) could be used to assess the chances of achieving elite athlete status. The PPARA C allele and PPARG Alaallele are predisposed to sprint and power or team events. PPARA G alleleis associated with endurance elite athletes status.